Dinamika Eksekusi Putusan Hakim Pasca Peninjauan Kembali dalam Perspektif Kepastian Hukum dan Perlindungan Hak Terpidana - Pardamean Harahap; Mochamad Yulian Fadhli Saputra; Muhamad Noval Faris Pratama; Ahmad Jafar Sidik (Pusat Riset dan Inovasi Nasional, 2025)
The implementation of the execution of judges' decisions after the Review (PK) raises a dilemma between legal certainty and the protection of the human rights of convicts. On the one hand, the execution of decisions that have had legal force is still necessary to maintain judicial authority and legal consistency. However, on the other hand, the PK as an extraordinary legal remedy opens up room for correction to potentially erroneous decisions, so that the execution cannot be carried out in a hurry. This research uses a normative-sociological approach by examining the Criminal Procedure Code (KUHAP), the Constitutional Court Decision, and the Supreme Court Circular Letter (SEMA) No. 7 of 2014, accompanied by an analysis of the practices of law enforcement officials. The results of the study show the need for regulatory synchronization and institutional reform so that post-PK executions reflect a balance between legal certainty, substantive justice, and the state's responsibility to protect the rights of convicts. Thus, this study emphasizes the importance of harmonization between legal norms and judicial practice to ensure that the execution of judgments not only upholds legal certainty, but also guarantees the protection of human rights.